1984
DOI: 10.1093/eurheartj/5.suppl_f.85
|View full text |Cite
|
Sign up to set email alerts
|

Myosin isoenzymes in human hypertrophic hearts. Shift in atrial myosin heavy chains and in ventricular myosin light chains

Abstract: (J Clin Invest 1982; 69: 816-825

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

1988
1988
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 20 publications
(23 reference statements)
2
18
0
Order By: Relevance
“…26 In addition, a number of cases of altered MLC1 ventricular expression in chronic cardiovascular disease states may be associated with significant functional consequences. Hypertrophied left ventricles of patients with ischemic, dilated, and hypertrophic cardiomyopathy express small amounts of atrial MLC1, [27][28][29] not normally present in the adult ventricle. Postsurgical return to a normal hemodynamic state decreased this ventricular expression of atrial MLC1.…”
Section: Discussionmentioning
confidence: 99%
“…26 In addition, a number of cases of altered MLC1 ventricular expression in chronic cardiovascular disease states may be associated with significant functional consequences. Hypertrophied left ventricles of patients with ischemic, dilated, and hypertrophic cardiomyopathy express small amounts of atrial MLC1, [27][28][29] not normally present in the adult ventricle. Postsurgical return to a normal hemodynamic state decreased this ventricular expression of atrial MLC1.…”
Section: Discussionmentioning
confidence: 99%
“…Permeabilized fiber studies from these mice showed a change in cardiac fiber function such that the incorporation of either ELC1 v or RLC2 v into atrial fibers caused decreased unloaded shortening velocity (787). Interestingly, myosin light-chain isoform switching, where the ventricular isoforms convert to the atrial light chains, has been documented in various human heart failure cases such as in congestive heart failure or in DCM (26, 601,794), suggesting important and divergent physiological roles in cardiac muscle for the ventricular versus atrial myosin light chains. The precise role of the different cardiac muscle MLC isoforms in cardiac function is not fully known.…”
Section: The Myosin Essential (Mlc-1/elc) and Regulatory (Mlc-2/ Rlc)mentioning
confidence: 99%
“…Therefore, this protein has been designated the embryonic myosin light chain (MLC) (16). The expression of this isoform was detected in the hypertrophied human ventricle (17). The hypertrophied right ventricle of children with tetralogy of Fallot (18) and the hemodynamically overloaded left ventricle of patients with valvular disease (19,20) also express a large amount of ALC 1 .…”
Section: Myofibrillar Assembly In Cardiac Hypertrophymentioning
confidence: 99%
“…Although ALC 1 becomes re-expressed in the overloaded human ventricle (17,19,20,22,74), β-MHC may combine with either ALC 1 and/or ventricular light chain 1 (VLC 1 ) to form two homodimers and one heterodimer in diseased human ventricles (23). The main consequence of ALC 1 re-expression in the ventricle is the increase of Ca 2+ sensitivity of the contractile apparatus (74).…”
Section: Myofibrillar Assembly In Congestive Hfmentioning
confidence: 99%